Anatomic symmetry of anterolateral thigh flap perforators: a computed tomography angiographic study. Issue 5 (5th March 2019) - Lu, David; Chan, Philip; Ferris, Scott; Shayan, Ramin; Angliss, Margaret; Bruscino‐Raiola, Frank
Abstract : Background: The anterolateral thigh flap is a workhorse reconstructive flap. Versatility in design is a key strength but perforator anatomy can be variable. Inability to locate perforators prompts consideration of contralateral thigh exploration. However, such exploration would be futile if the absence of perforators proves symmetrical. This study assesses the symmetry of anterolateral thigh flap vasculature using computed tomography angiography (CTA). Methods: A retrospective analysis of 20 bilateral thigh CTAs was performed. Each limb was assessed for number, course, location and size of perforators. Only vessels >0.5 mm in size at origin were included. Location was standardized between patients using perforator distance/thigh length ratio. Results were analysed using Wilcoxon signed‐rank test. Results: In each thigh, the average number of perforators was 3.58 and average perforator distance/thigh length ratio was 0.358 ± 0.08. Between both limbs of the same patient, the mean difference in number of perforators was 0.55 ( P = 0.002), and difference in average perforator size was 0.3 mm ( P < 0.001). Average perforator location differed by a mean of 3% of thigh length ( P < 0.001) between thighs. Conclusion: While average vessel size and location appear similar, there does not appear to be symmetry in the number of perforators. Surgical exploration of the contralateral thigh in an absence of perforators should be considered. In patients where abnormal anatomy is expected, mapping with CTA could be considered to reduce morbidity associated with unsuccessful surgical exploration and dissection. Abstract : This study assesses the symmetry of anterolateral thigh flap vasculature using computed tomography angiography in order to guide flap harvest, especially if no perforators are identified initially. Results show that while average vessel size and location appear similar, there does not appear to be symmetry in the number of perforators. Surgical exploration of the contralateral thigh in an absence of perforators should be considered.